Beyond the Pure and the Authentic: Indigenous modernity in Andean Bolivia. (December 2015) - Ravindran, Tathagatan
This article explores the various forms in which indigenous practices and worldviews articulate with the modern, leading to the formation of a distinct indigenous modernity. It reveals that the construction of indigeneity in terms of purity and distance from the modern is being challenged by urban Aymaras (indigenous people of the Andean region of South America) who affirm their Aymara identity without enacting purity. This explains why modernizing and developmentalist assumptions are part of their discourse of indigenous liberation. This new indigenous political discourse stands in tension with a postdevelopmentalist indigenous politics, which is the product of a different engagement with modernity. Different encounters with colonialism and modernity have created multiple indigenous modernities with contradictory perspectives on indigenous political liberation and well-being. The article is a product of 22 months of ethnographic research in the city of El Alto between 2010 and 2014 that included participant observation in multiple neighborhoods of El Alto, 85 semistructured interviews and 5 focus groups.